Evaluation of the Entomopathogenic potential of Beauveria bassiana, Metarhizium anisopliae and Isaria fumosorosea for management of Cosmopolites sordidus Germar (Coleoptera: Curculionidae) - Kisaakye, J.; Fourie, H.; Coyne, D.; Cortada Gonzales, L.; Masinde, S.; Subramanian, S.; Haukeland, Solveig (MDPI, 2021)
The banana weevil (BW), Cosmopolites sordidus, is the main coleopteran pest of banana, causing up to 100% yield loss. In this study, we screened 20 isolates of entomopathogenic fungi (EPF) for the management of BW. In the lab, eight Beauveria bassiana isolates caused >50% mortality of the adult BW, whereas Metarhizium anisopliae and Isaria fumosorosea isolates were less pathogenic. B. bassiana isolates ICIPE 648, ICIPE 660 and ICIPE 273 were the most pathogenic, killing ≥80% of adult BW. B. bassiana isolate ICIPE 622 yielded the highest spores per BW cadaver (1.84 × 108 spores), followed by ICIPE 660, ICIPE 273 and ICIPE 648—1.17 × 108, 3.8 × 107 and 3.6 × 107 spores, respectively. ICIPE 273 had the shortest LT50 (5.3 days) followed by ICIPE 648 (9.8 days) and 660 (11.1 days). Similarly, the LC50 values for the three isolates were 5.18 × 107, 5.49 × 107 and 5.2 × 107 spores mL−1, respectively. In the field, ICIPE 273 and ICIPE 648 had the highest (31.3%) and lowest (20.8%) pathogenicity, respectively. This study indicates that the B. bassiana isolates ICIPE 273, ICIPE 648 and ICIPE 660 are potential candidates for the environmentally sustainable management of BW.